A robust verification system for recruitment process by using blockchain technology. (7th January 2021) - Rathor, Sandeep; Agrawal, Ankit
In this competitive world, it is hard to get a job. It requires some specific qualifications and experience according to the post. If a person is not fulfilling these required entities, then not able to apply for that post. Therefore, some people, who are not eligible may use different forgery approaches like fake mark sheets, fake experience certificates, fake medical certificates, etc. However, despite being these fake certificates, some people may have a criminal background also. Therefore, large numbers of resources are required to verify the educational records, criminal background, and experience of a person. Therefore, the proposed system provides an efficient solution to these problems using blockchain technology. In the proposed work, we used three different modules like college, organisation, and police. The college is responsible for providing academic qualifications and the organisation is responsible for providing experience while police are responsible for proving and verification of the criminal record. The proposed system is implemented on the Ethereum blockchain platform and effectively can be used by the organisations for verifying the record of their employees.